LEGAL PROBLEMATICS OF RETURNING ASSETS (CONFISCED OBJECTS) THE DEFEND DIED IN A MONEY LAUNDERING CRIME CASE - Parinduri, Hamdani; Sunarmi, Sunarmi; Siregar, Mahmul; Trisna, Wessy (NOMOI Law Review, 2024)
The applicable legal instruments in Indonesia have not been able to regulate all activities to return existing criminal assets with asset recovery/return of assets resulting from crime, although in Law Number 7 of 2000, asset return has been ratified in accordance with UNCAC. With Law Number 8 of 2010 concerning TPPO, a person who commits an act to hide or disguise criminal assets is criminalized. The problem is how is the proof of money laundering crimes against the return of assets (confiscated objects) of deceased defendants? How is the analysis of the judge's considerations and decisions regarding the return of assets (confiscated objects) of deceased defendants in the trial process based on the Medan District Court Decision No. 1252/Pid.Sus/2020/PN Mdn jo. Medan High Court Decision No. 391/Pid.Sus/2021/PT Mdn jo. Supreme Court Decision No. 3856 K/Pid.Sus/2022? The research method used in this study is the Normative Research with approach method used in this research is the statutory approach.. From the results of the analysis, it is known that in the event of the death of the defendant, based on the provisions of the Criminal Procedure Code Article 77 Regarding the deceased suspect (suing to his heirs) as regulated in Article 33 of the Corruption Law and the deceased defendant (suing to his heirs) as regulated in Article 34 of the Corruption Law, there are 3 scopes that must be fulfilled without criminalization.